Assessing The Effects of Personality and Work Ability on Employee Performance at The General Bureau Office of The Regional Secretariat of West Sulawesi Province - Aisyah, Aisyah; Martini, Andi Indra; Rasyid, Roshita Amalyah (JEM17: Jurnal Ekonomi Manajemen, 2025)
This study aims to analyze the influence of personality and work ability on employee performance (EP) at the General Bureau Office of the Regional Secretariat of West Sulawesi Province (GBORS-WSP). A quantitative approach using an associative design was applied to analyze the causal relationships among the study variables. The population consisted of all 76 employees, and using the total sampling as the sampling technique. Data collection procedures involved direct obeservation, structured intervies, and questionnaires measured using a Likert-type scale. The data were processed thorugh multiple linear regression analysis with the statistical support from SPSS version 26. The results revealed that both personality and work ability have a positive and significant effect on EP, both partially and simultaneously. The coefficient of determination also indicates that personality and work ability explain a substantial portion of the variation in EP, while more than half is influenced by other factors. Therefore, enhancing positive personality traits and improving work ability are key factors in increasing EP within the government bureaucracy environment. Keywords: Employee Performance; Personality; Work Ability.